PENGARUH PENERAPAN SISTEM E-COMMERCE TERHADAP PENJUALAN JASA PADA HOTEL TIATIRA KENCANA MAKASSAR - Mariah Mariah (Jurnal Bisnis dan Kewirausahaan, 2018)
The aim of this study was to knowing the effect of the application e-commerce systems to the level of sales service in the hotel Hotel Tiatira Kencana Makassar and to knowing the influence of information, marketing and security in e-commerce to increase sales of services in the Hotel Tiatira Kencana Makassar. The research location at Hotel Tiatira Kencana Makassar Jl. Dr.Sutomo No.31. This study using multiple linear analytical test methods of customer / guest on Hotel Tiatira Kencana Makassar . The results showing that the hypothesis of e-commerce affect increase in sales of services in Hotel Tiatira Kencana Makassar proven, and analysis all the three independent, there are two most dominant factor influencing the increase in sales of services in the Hotel Tiatira Kencana Makassar, the variable is information (X1) and security (X3). Whereas the marketing variables (X2) considered in this study no significant effect on the increase in sales of services in the Hotel Tiatira Kencana Makassar.